2018
DOI: 10.1007/s13555-018-0270-1
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation-Based Workshop to Improve Dermatologists’ Communication Skills: A Pilot for Continuing Medical Education

Abstract: Introduction Communication skills influence the quality of health care and patient experience; both may affect provider reimbursement. There are few opportunities available for practicing physicians to receive direct feedback on communication in patient encounters. The purpose of this simulation-based patient encounter workshop was for dermatologists to practice and obtain feedback on their communication skills. Methods In March 2016, dermatologists participated in a wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…28,29 Interventions on adherence and MRF need to enhance communication with the patient, as shown in several studies that demonstrated a correlation between effective pharmacist-patient communication and improved patient health outcomes, like affecting physical and emotional health, patient understanding of medical issues, adherence to treatment regimens and patient satisfaction with healthcare. [30][31][32] In addition, due to the behavioral characteristics of adherence and MRF, they require learning of theoretical models of behavior change, this models can be taught easier using a practical case. However, some aspects of the videos should be improved as shown in the item "It properly simulates the reality".…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Interventions on adherence and MRF need to enhance communication with the patient, as shown in several studies that demonstrated a correlation between effective pharmacist-patient communication and improved patient health outcomes, like affecting physical and emotional health, patient understanding of medical issues, adherence to treatment regimens and patient satisfaction with healthcare. [30][31][32] In addition, due to the behavioral characteristics of adherence and MRF, they require learning of theoretical models of behavior change, this models can be taught easier using a practical case. However, some aspects of the videos should be improved as shown in the item "It properly simulates the reality".…”
Section: Discussionmentioning
confidence: 99%
“…This shows the importance of fostering communication skills in dermatology residents, especially low-rated skills like allowing the patient to share their narrative thread, summarizing the patient's history from the provider and assessing patient understanding. 8 Using visual arts education can also benefit clinical communication with patients having chronic diseases. Patients prefer to be treated by dermatologists who are attentive listeners.…”
Section: A Nationwide French Cohort Study On 3154 Patients With Atopi...mentioning
confidence: 99%